IMPLEMENTASI SISTEM INFORMASI SUMBER DAYA MANUSIA DALAM MENINGKATKAN DISIPLIN KERJA SERTA DAMPAKNYA TERHADAP KUALITAS PELAYANAN INTERNAL (Survei pada Aparatur Sipil Negara di Instansi Pemerintah Kota Medan) - Panjaitan, Ferry (Jurnal Manajemen dan Bisnis, 2019)
The purpose of this study is to examine the implementation of human resource information systems that will affect the discipline of work and which give impact to improving service quality. Research method used in this research is descriptive analysis and verification analysis. Descriptive analysis method and verifikatif analysis was chosen in this study, because it is necessary to know or describe every variable under studyHuman resources information system in Medan city administration can not be implemented properly where the implementation of human resource information system still has some problems such as the problem of low human resources ability in running information systems, slow internet access, less supportive hardware, and others .ASN in Medan city administration does not have high discipline which is indicated by the ineffective use of time, the number of ASN disobedient to the peratiran which resulted in many employees are given government discipline sanction.Quality of internal service in the city government of Medan is now good where already enough ASNs are already satisfied with the internal services they receive.Implementation of human resource information system have a positive and significant influence to ASN discipline in Medan city administration, ASN work discipline has significant effect to internal service quality in Medan city government, Implementation of human resource information system has significant effect to internal service quality in Medan city government, Implementation Human Resource Information System has no significant effect on internal service quality in Medan City government through work discipline.